Potential risk of tamoxifen: gut microbiota and inflammation in mice with breast cancer - Li, Hailong; Gao, Xiufei; Chen, Yian; Wang, Mengqian; Xu, Chuchu; Yu, Qinghong; Jin, Ying; Song, Jiaqing; Zhu, Qi (Frontiers in Oncology, 2023)
Objective Tamoxifen is an effective anti-tumor medicine, but evidence has been provided on tamoxifen-related inflammation as well as its impact on gut microbiota. In this study, we aimed to investigate tamoxifen-induced gut microbiota and inflammation alteration. Methods We established a BC xenograft mouse model using the MCF-7 cell line. 16S rRNA gene sequencing was used to investigate gut microbiota. qRT–PCR, western blotting, and cytometric bead array were used to investigate inflammation-related biomarkers. Various bioinformatic approaches were used to analyze the data. Results Significant differences in gut microbial composition, characteristic taxa, and microbiome phenotype prediction were observed between control, model, and tamoxifen-treated mice. Furthermore, protein expression of IL-6 and TLR5 was up-regulated in tamoxifen-treated mice, while the mRNA of Tlr5 and Il-6, as well as protein expression of IL-6 and TLR5 in the model group, were down-regulated in the colon. The concentration of IFN-γ, IL-6, and IL12P70 in serum was up-regulated in tamoxifen-treated mice. Moreover, correlation-based clustering analysis demonstrated that inflammation-negatively correlated taxa, including Lachnospiraceae-UCG-006 and Anaerotruncus, were enriched in the model group, while inflammation-positively correlated taxa, including Prevotellaceae_UCG_001 and Akkermansia, were enriched in the tamoxifen-treated group. Finally, colon histologic damage was observed in tamoxifen-treated mice. Conclusion Tamoxifen treatment significantly altered gut microbiota and increased inflammation in the breast cancer xenograft mice model. This may be related to tamoxifen-induced intestinal epithelial barrier damage and TLR5 up-regulation.